Chemical reactor inherent safety index at preliminary design stage. (December 2018) - Athar, Muhammad; Zaidi, Nor Ayuni Binti; Shariff, Azmi Mohd; Buang, Azizul; Khan, Muhammad Ishaq
Abstract: The design inadequacy of chemical reactor has caused many major accidents in process industries. The absence of safety analysis for chemical reactor especially in the early design stage is one of the reasons for faulty designs. Inherent safety can be used to perform the safety analysis at preliminary design phases. However, the literature is deficient in reporting inherent safety assessment method for chemical reactors. Therefore, this paper introduces a new indexing method for inherently safety assessment of chemical reactors at the preliminary design stage. Chemical Reactors Inherent Safety Index (CRISI) is based on three sub-indices; chemical index, process index and reaction index. These sub-indices are estimated through scores of numerous parameters in each dimension. For the unacceptable score, the process conditions are changed according to the favorable reaction conditions. CRISI is estimated for all combination of process conditions and lowest CRISI value indicates the inherently safer design of the reactor.